Elasticity of demand for petrol in Ireland - O"Riordan, WK (Economic & Social Studies, 1972)
This brief study attempts to estimate the price elasticity of demand for petrol in Ireland at the present time. The statistic is not without importance. Alcohol, tobacco and petrol are the three main sources of indirect tax revenues in this country. Estimates of the price elasticities of the first two are already available so it seems worth making an effort to finish the task. Ignorance of price elasticities probably does little harm if we are prepared to let the price system work unhampered. But when we begin to interfere, to the extent that is normal in the case of such goods, it is wise to have,some idea about the likely result.of our actions.
Keywords: Petrol Demand; Ireland